A bactericidal antibody to Borrelia burgdorferi is directed against a variable region of the OspB protein. - Sadziene, A (1994)
Borrelia burgdorferi, an agent of Lyme disease, is killed by some monoclonal antibodies in the absence of complement or phagocytes. In the present study, the bactericidal action of monoclonal antibodies against B. burgdorferi and B. hermsii, a cause of relapsing fever, was further characterized. H6831, an antibody recognizing the OspB proteins of some B. burgdorferi strains, and H4825, an antibody specific for one serotype of B. hermsii, were purified, and Fab fragments of the antibodies were prepared. In time-kill studies, more than 99.9% of strain B31 B. burgdorferi cells were killed after 30 min of exposure to H6831 Fab fragments. The MBC of the Fab fragments was 10 micrograms/ml. Electron microscopy revealed that the bactericidal Fab fragments produced numerous blebs and cell lysis of the borrelias for which they were specific. To identify the epitope for H6831, the OspB sequences of H6831-susceptible and -resistant strains and mutants were determined. The deduced OspB proteins of all H6831-resistant strains and mutants differed from the strain B31 OspB at residue 253. Murine antisera raised against a 21-mer synthetic peptide representing the region around residue 253 were specific for strain B31 by Western blot (immunoblot) and growth inhibition assays. Furthermore, the antipeptide serum inhibited the binding of H6831 to whole borrelias. These findings indicated that the linear component of the bactericidal antibody's epitope was located at or near residue 253.